The association of serum irisin with anthropometric, metabolic, and bone parameters in obese children and adolescents - Kim, Shin-Hee; Kim, Sung Eun; Kim, Seulki; Ahn, Moon Bae; Cho, Won Kyoung; Cho, Kyoung Soon; Jung, Min Ho (Frontiers in Endocrinology, 2024)
Background: Irisin is an adipomyokine secreted by muscle and adipose cells, and it plays a role in glucose, fat, and bone metabolism. This study aimed to determine the correlation of serum irisin levels with anthropometric, metabolic, and bone parameters in obese children and adolescents. Methods: This single-center study included 103 Korean children and adolescents: 54 (52.4%) obese participants with a body mass index (BMI) ≥95th percentile and 49 (47.6%) healthy controls with BMI within the 15th to 85th percentile. Various parameters were measured, including fasting blood glucose, fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), triglyceride and glucose (TyG) index, lipid profile, alkaline phosphatase (ALP), osteocalcin, and 25(OH)-Vitamin D levels. Bone mineral density (BMD) was measured using dual-energy X-ray absorptiometry (DEXA) in 33 healthy subjects. Results: Serum irisin was significantly higher in the obese group than in the control group (mean 18.1 ± 3.5 vs. 16.2 ± 2.0 ng/mL; p = 0.001). Serum irisin level was positively correlated with chronological age (r = 0.28; p = 0.004), height SDS (r = 0.24; p = 0.02), BMI SDS (r = 0.37; p < 0. 001), fasting glucose (r = 0.27; p = 0.007), fasting insulin (r = 0.23; p = 0.03), HOMA-IR (r = 0.21; p = 0.04), osteocalcin (r = 0.27; p = 0.006) and negatively correlated with HDL cholesterol (r = -0.29; p = 0.005). All these correlations were evident in obese subjects but not in healthy subjects. ALP and 25(OH)-Vitamin D were unrelated to irisin levels. Among 33 healthy subjects, total body-less head (TBLH) BMD Z-score was positively correlated with serum irisin (r = 0.39; p = 0.03), osteocalcin (r = 0.40; p = 0.02), fasting insulin (r = 0.39; p = 0.04), and HOMA-IR (r = 0.38; p = 0.047). Conclusions: This study demonstrated an association between irisin levels and glucose, lipid, and bone parameters in children and adolescents. Our findings suggest that irisin has a potential role in metabolic disorders and bone health in obese children and adolescents.